2020
DOI: 10.1149/1945-7111/ab6984
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Cr2O3 in Molten Fluorides with Different ZrF4 Contents and Fluoroacidities

Abstract: This work focused on the stability of the protective Cr 2 O 3 layer formed on alloys in molten fluorides with different fluoroacidities and ZrF 4 contents. Results showed that fluoroacidity only slightly affected Cr 2 O 3 due to its stability in basic FLiNaK and neutral FLiBe melts. When more than 1.1 mol% ZrF 4 was added to FLiNaK, the new structure [ZrF 7 ] 3− formed by the interaction of ZrF 4 and F − could be detected by Raman Spectroscopy and X-ray diffraction, and Cr 2 O 3 solubility in FLiNaK-ZrF 4 incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
4
14
0
Order By: Relevance
“…However, with respect to the FLiNaK-Cr 2 O 3 system, the solubility of Cr 2 O 3 in FLiNaK is a key factor affecting chromium electroextraction. Our previous investigation and related reports [23][24][25] pointed out that the Cr 2 O 3 solubility in molten uorides was relatively low. For example, the solubility of Cr 2 O 3 in molten FLiNaK and FLiBe at 600 °C was as low as 122 ppm and 183 ppm, respectively, 23 which makes the electrolysis difficult and challenging.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, with respect to the FLiNaK-Cr 2 O 3 system, the solubility of Cr 2 O 3 in FLiNaK is a key factor affecting chromium electroextraction. Our previous investigation and related reports [23][24][25] pointed out that the Cr 2 O 3 solubility in molten uorides was relatively low. For example, the solubility of Cr 2 O 3 in molten FLiNaK and FLiBe at 600 °C was as low as 122 ppm and 183 ppm, respectively, 23 which makes the electrolysis difficult and challenging.…”
Section: Introductionmentioning
confidence: 84%
“…Our previous investigation and related reports [23][24][25] pointed out that the Cr 2 O 3 solubility in molten uorides was relatively low. For example, the solubility of Cr 2 O 3 in molten FLiNaK and FLiBe at 600 °C was as low as 122 ppm and 183 ppm, respectively, 23 which makes the electrolysis difficult and challenging. Therefore, it is necessary to nd suitable additives to increase Cr 2 O 3 solubility in molten uorides.…”
Section: Introductionmentioning
confidence: 84%
“…LiF–BeF 2 (66.7–33.3 mol%) eutectics were provided by the Shanghai Institute of Applied Physics, Chinese Academy of Sciences. 10 Since LiF–ThF 4 was more easily dissolved in FLiBe, the molten salt of LiF–ThF 4 was prepared first. 11 About 2.8 g of LiF was mixed with 10.2 g of ThF 4 in a nickel crucible with a diameter of 2.5 cm.…”
Section: Methodsmentioning
confidence: 99%
“…2, which was described in detail in our previous studies. 7,8,16,17,20,21,24 The whole experiment was conducted in a glove box protected by dry argon atmosphere (99.999%), and the oxygen and water contents in the glove box were both strictly controlled below 0.5 ppm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…ZrF 4 can also increase the solubility of oxides because of its strong affinity toward oxygen ions. Song et al21 have studied the dissolution behavior of chromium sesquioxide (Cr 2 O 3 ) in various molten uorides and found that the ZrF 4 additive remarkably increases the solubility of Cr 2 O 3 by 19 and 2 times in FLiNaK and FLiBe molten salt, respectively, most likely yielding the dissolution product of [ZrO x F y ] 4À2xÀy complex species. Peng et al…”
mentioning
confidence: 99%